Labour and Neonatal Outcome in Small for Gestational Age Babies Delivered Beyond 36+0 Weeks: A Retrospective Cohort Study - K. E. Boers; J. A. M. van der Post; Ben W. J. Mol; J. M. M. van Lith; S. A. Scherjon (Journal of Pregnancy)
Objective. Small for gestational age (SGA) is associated with increased neonatal morbidity and mortality. At present, evidence on whether these pregnancies should be managed expectantly or by induction is lacking. To get insight in current policy we analysed data of the National Dutch Perinatal Registry (PRN). Methods. We used data of all nulliparae between 2000 and 2005 with a singleton in cephalic presentation beyond 36+0 weeks, with a birth weight below the 10th percentile. We analysed two groups of pregnancies: (I) with isolated SGA and (II) with both SGA and hypertensive disorders. Onset of labour was related to route of delivery and neonatal outcome. Results. Induction was associated with a higher risk of emergency caesarean section (CS), without improvement in neonatal outcome. For women with isolated SGA the relative risk of emergency CS after induction was 2.3 (95% Confidence Interval [CI] 2.1 to 2.5) and for women with both SGA and hypertensive disorders the relative risk was 2.7 (95% CI 2.3 to 3.1). Conclusion. Induction in pregnancies complicated by SGA at term is associated with a higher risk of instrumental deliveries without improvement of neonatal outcome. Prospective studies are needed to determine the best strategy in suspected IUGR at term.